Housing and health in Germany. Issue 3 (13th February 2004) - Pollack, C E; von dem Knesebeck, O; Siegrist, J
Abstract : Study objectives: To examine the association between housing tenure and self rated health, controlling for socioeconomic measures and testing the mediating effects of physical features of the home, pollution in the local environment, and relationships with neighbours. Design: Cross sectional panel study with people nested within households. Analyses were performed using multilevel methods. Setting: Population based sample in Germany. Participants: People aged 16 or older were interviewed in the 1999 wave of the socio-economic panel study (n = 14 055) and nested within households (n = 7381). Main results: 44.0% of the population lived in homes that they owned. In bivariate analyses, women, people who live in apartment buildings, reside near cities, live in crowded homes, have homes in need of renovation, report higher pollution, and have distant contact with neighbours are more likely to live in rented homes. In multilevel analyses, renting a home was found to be associated with poor self rated health (OR 1.48, 95% CI 1.31 to 1.68). This relation persisted after controlling for education and income and was partially mediated by the need for household renovation, the perception of air and noise pollution in the local area, and distant relationship with neighbours, all of which were significantly associated with self rated health. Conclusions: This study provides evidence that home ownership is significantly associated with self rated health in Germany, and this relation may be, in part, mediated by physical and social features of home and neighbourhood.